2020
DOI: 10.1002/art.41189
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine Deiminase Autoimmunity and the Development of Anti–Citrullinated Protein Antibody in Rheumatoid Arthritis: The Hapten–Carrier Model

Abstract: Objective. The presence of autoantibodies to citrullinated proteins (ACPAs) often precedes the development of rheumatoid arthritis (RA). Citrullines are arginine residues that have been modified by peptidylarginine deiminases (PADs). PAD4 is the target of autoantibodies in RA. ACPAs could arise because PAD4 is recognized by T cells, which facilitate the production of autoantibodies to proteins bound by PAD4. We previously found evidence for this haptencarrier model in mice. This study was undertaken to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Our patient had antibody responses and Tcell proliferation to PAD4 and peptide 8 from PAD4, consistent with the haptencarrier model in rheumatoid arthritis. 10 To the best of our knowledge, this is the first definitive case of ACPApositive rheumatoid arthritis developing after SARSCoV2 infection (ie, with samples taken before and after arthritis onset), with infection as a poten tial trigger for epitope spreading and onset of clinical rheumatoid arthritis symptoms.…”
Section: First Flare Of Acpa-positive Rheumatoid Arthritis After Sarsmentioning
confidence: 81%
See 1 more Smart Citation
“…Our patient had antibody responses and Tcell proliferation to PAD4 and peptide 8 from PAD4, consistent with the haptencarrier model in rheumatoid arthritis. 10 To the best of our knowledge, this is the first definitive case of ACPApositive rheumatoid arthritis developing after SARSCoV2 infection (ie, with samples taken before and after arthritis onset), with infection as a poten tial trigger for epitope spreading and onset of clinical rheumatoid arthritis symptoms.…”
Section: First Flare Of Acpa-positive Rheumatoid Arthritis After Sarsmentioning
confidence: 81%
“…Our patient had antibody responses and T-cell proliferation to PAD4 and peptide 8 from PAD4, consistent with the hapten-carrier model in rheumatoid arthritis. 10 …”
mentioning
confidence: 99%
“…Altogether, these data demonstrate that the generation of an autoimmune response to citrullinated proteins and peptides is a complex process. Several hypotheses have been proposed including autoimmune responses to the PAD4 protein in which the PAD4 acts as carrier and the citrullinated proteins act as a hapten [ 58 , 59 ], as well as a potential role of non-SE MHC-II alleles participating in the presentation of citrullinate peptides [ 60 ]. Additionally, citrullination is only one of many PTMs that can occur to proteins, raising the possibility that autoimmune T cell responses could be targeting multiple neo-antigens that have been generated at the site of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Martinez-Prat et al [ 46 ] showed that PAD4 as a cognate antigen to induce anti-PAD4 autoantibodies in RA patients was associated with specific clinical features that can help improve disease diagnosis. In consideration of PAD4 as an effector and target molecule in RA pathogenesis, Auger et al [ 47 ] further proved that ACPAs are induced after PAD4 is recognized by T cells to facilitate the production of antibodies against “citrullinated peptides” bound by PAD4, mimicking a so-called “hapten-carrier” model. Recently, Darrah et al [ 48 ] investigated the antibodies against native and auto-citrullinated PADs in patients with RA.…”
Section: The Abnormal Expression and Functions Of Peptidylarginine Deiminase 2 (Pad2) And 4 (Pad4) In Generating Apcas And Anti-pad Autoamentioning
confidence: 99%